The monitoring of Cu contaminated water through potato peel charcoal and impact on enzymatic functions of plants. (1st December 2017) - Azmat, Rafia; Moin, Sumeira
Abstract: Enzymes are a biological catalyst, an important protein that accelerates the most biochemical reactions of a plants cell, investigated in this article as a provoked biomarkers under Cu stress. The study was conducted in comparison of (a) Control, (b) Cu stress plants and (c) treated plants in the greenhouse. The treated plants were grown in recycled water, prepared at laboratory scale using potato peel charcoal (PPC) as a sorbent. Weekly monitoring of various enzymes in plants (b) up to three months showed that peroxidase activity enhanced in comparison to control and treated plants, while protease, amylase and, nitrate and nitrite reductase were reduced. The enzymatic disorder under Cu stress reflects the generation of reactive oxygen species (ROS) and the failure of the key and um-lock action of enzymes for complex molecules, which plays a critical role in the biochemical reaction of plants to grow. Elevated peroxidase activity in roots and leaves of plant (b) indicated that it aid in minimizing the damages under activated ROS. The observed reduced activities of protease, amylase, nitrate and nitrite reductase presented that redox active metal (Cu) interfere at the molecular level and damages the normal C and N mechanism of development of plants (b) under abiotic stress over control. The ROS conflicts in plants (b) due to high accumulation of Cu was resolved by checking the mobility of Cu on PPC surface from Cu-contaminated wastewater. It appeared as a normal growth rate in plant (c), similar to that of plants grown in tap water (Plants a). The remediation of enzymatic disorder through Surface Science Technology (SST) in plant (c) validated that wastewater can easily manage through sorption of Cu metal on the PPC surface. The decontamination through SST showed that the wastewater could be restored economically which can use in irrigation without harmful impact on plant growth regulatory system. Graphical abstract: Highlights: Investigation of enzymes activity as vital part of plant growth under abiotic stress. Restoration of contaminated water using PPC as a cost effective technology. Remediation of enzymatic activities followed to normal growth of plant in recycled water.